Individual Differences in Fear and Social Reinstatement Behaviours in Laying Hens - Ghareeb, K.; Awad, W.A.; Niebuhr, K.; Bohm, J.; Troxler, J. (International Journal of Poultry Science, 2008)
Individual differences in behavioural responses are of growing interest in behavioural studies. The present study investigated the consistency of the individual differences over time and across social (social reinstatement responses) and non social test situations (tonic immobility response). Three breeds of commercial hybrid layers (ISA Brown, Lohmann Tradition and Lohmann Silver) were reared from hatch to 37 weeks of age. Individual birds were subjected to tonic immobility test at 3, 5, 7, 10, 11, 15, 16, 20, 24, 35 and 37 wk old and to runway test of sociality at 3, 5, 10, 16, 20 and 37 wk old. Fearfulness did not show breed differences either in the overall means or in a certain tested age. However, ISA Brown had a higher latency to emerge to a runway than LT (16 and 20 wk) and LS (at 37 wk). In addition, ISA Brown hens had a higher latency to reinstate with their companion than LS (10 and 37 wk). The individual ranks for behavioural traits of fear and sociality were consistent over time. These results indicate fear and sociality responses are behavioural strategies used by individuals in certain test situation when repeated. Moreover, the duration of TI response was positively correlated to both sociality traits (latency to emerge and reinstate with a companion) indicating that birds had overall behavioural traits that were consistent across different contexts. This suggests that hens can be categorized into behavioural types or styles based on their test responses. The highly fearful birds (longer TI duration) had a higher latency to emerge and reinstate with their companions (reactive style) and the less fearful birds (shorter TI duration) had a lower latency to emerge and socially reinstate with their companions (proactive style). In conclusion, these individual differences are consistent over time and the behaviour of hens in one test can predict their behaviour in other test situation. Thus it could be used to assess individual hens and potentially be used in a breeding program to select a hen with more desirable personality traits.